2011
DOI: 10.1161/circep.110.958322
|View full text |Cite
|
Sign up to set email alerts
|

Primary Prevention of Sudden Cardiac Death in Silent Cardiac Sarcoidosis

Abstract: Background— Cardiac involvement in sarcoidosis is often silent and may lead to sudden death. This study was designed to assess the value of programmed electric stimulation of the ventricle (PES) for risk stratification in patients with sarcoidosis and evidence of preclinical cardiac involvement on imaging studies. Methods and Results— Patients with biopsy-proven systemic sarcoidosis but without cardiac symptoms who had evidence of cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
0
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(105 citation statements)
references
References 14 publications
0
96
0
9
Order By: Relevance
“…Only 1 patient died from the 68 whose PES was negative and none had symptomatic VT or required an ICD after 5 years of follow-up. 42 Similarly, in 27 systemic sarcoidosis patients with suspected cardiac involvement, Aizer et al found a hazard ratio, for SCD or ICD shock, of 6.3 (95% confidence interval: 1.81-21.95) in subjects with spontaneous VT. 41 They also found a hazard ratio of 6.97 (95% confidence interval: 1.27-38.27) in patients with inducible VT by PES but no history of spontaneous VT. These studies demonstrate that PES can detect electrically labile myocardium in subclinical CS.…”
Section: Programmed Electrical Stimulationmentioning
confidence: 96%
See 2 more Smart Citations
“…Only 1 patient died from the 68 whose PES was negative and none had symptomatic VT or required an ICD after 5 years of follow-up. 42 Similarly, in 27 systemic sarcoidosis patients with suspected cardiac involvement, Aizer et al found a hazard ratio, for SCD or ICD shock, of 6.3 (95% confidence interval: 1.81-21.95) in subjects with spontaneous VT. 41 They also found a hazard ratio of 6.97 (95% confidence interval: 1.27-38.27) in patients with inducible VT by PES but no history of spontaneous VT. These studies demonstrate that PES can detect electrically labile myocardium in subclinical CS.…”
Section: Programmed Electrical Stimulationmentioning
confidence: 96%
“…41,42 Programmed electrical stimulation (PES) has the potential to identify CS patients with electrical instability and may help to determine if patients should get an ICD. 6 Mehta et al studied 76 patients with extracardiac sarcoidosis and found 8 with a positive study, and all had ICDs placed.…”
Section: Programmed Electrical Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Mehta et al 16 evaluated electrophysiological testing for risk stratification in patients with asymptomatic CS. In that study, the majority of patients with inducible VT had a reduced LVEF, and therefore, the patient population at risk was different than in the present study.…”
Section: Risk Stratification Of Patients With Cardiac Sarcoidosismentioning
confidence: 99%
“…22 The decision regarding ICD insertion is hampered by limited tools for patient risk stratification and a lack of knowledge regarding the true prevalence of ventricular arrhythmia in this population. Programmed ventricular stimulation has been shown to have some use in this regard, [23][24][25] but there are limited studies in this area and the long-term prognostic significance of a normal study remains unclear.…”
Section: Downloaded Frommentioning
confidence: 99%